Pesta Rakyat pada Peringatan Hari Ulang Tahun Kemerdekaan Republik Indonesia Ekspresi Kultural dalam Format Seremonial Kenegaraan - Wahyudiyanto Wahyudiyanto (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2026)
Ceremonial always accompanies various important events for institutions, and even a nation. They are held several times to mark the institution's existence due to significant historical events. The Indonesian struggle for independence is a historical event, and commemorating Independence Day is a way to remember this patriotic moment. Governments at the central, regional, and local levels, down to the village, hamlet, and neighborhood unit (RT/RW) levels, celebrate it with great enthusiasm. Ceremonial is a state celebration packaged in the form of a ceremony, so it must be formal, sacred, and solemn because it uses symbols and important state guests, as well as relaxed and entertaining, therefore entertainment is presented in the form of art. Klampis Anom Village, Sukolilo, Surabaya, held a state ceremonial celebration to commemorate the 80th anniversary of Indonesian Independence Day on August 17, 2025. The entertainment from the STKW Surabaya Dance Arts Study Program in the form of community service appeared compact, pithy, and enchanting as seen from the enthusiasm of the audience who did not move from their seats until the performance was over.